Elemen sumbangan dalam pembahagian harta sepencarian : pengalaman kaum wanita Melayu di Malaysia / Mohd Anuar Ramli, Mohd Norhusairi Mat Hussin and Mohammad Aizat Jamaludin - Ramli, Mohd Anuar; Mat Hussin, Mohd Norhusairi; Jamaludin, Mohammad Aizat (Universiti Teknologi MARA, Pulau Pinang & UPENA, 2012)
Women are complementary to men. This kind of mutual relationship has led to its positive expression as a "gender friendly" element, especially in the development of Islamic law within the Malay World. On the whole, women in the Malay Archipelago have survived the socio-cultural construction differently compared to women in other areas. Historically, besides their primary task in the domestic sphere, the Malay-Muslim women have also been involved in the economic sector, particularly in helping their husbands to fulfil household budgets. In accordance with the climatic conditions and geographical area, agriculture was the main economic sector in the Malay Archipelago. This factor has stimulated women to actively participate in this sector. As a result, from this scenario, there is a popular dictum among them "segendong sepikol" or “harta sepencarian”, which demonstrates the distribution of property between husband and wife. This is due to the existence of jointly acquired property between the two parties. This distribution of property is parallel with the contribution of women, either directly or indirectly, in supporting the household finance. It allows them to get their right, either 1/2 or 1/3, etc., in the division of property. Lately, couples tend to choose sulh (conciliation) as a solution. Remarkably, this practice is only available in the Malay Archipelago, particularly among the Malay-Muslim community in Malaysia. Hence, this socio-legal article attempts to discuss the element of contribution of women in Malaysia to the household finance in which, eventually, they get provisions of the rights of jointly-acquired property claims in Malaysia